Empis s. str. (Diptera: Empididae) from Egypt, Israel and Syria: notes on some species described by J.E. Collin and a key to species - Shamshev, Igor V. (Zootaxa, 2020)
The type material of three Empis s. str. species described by J.E. Collin from Egypt and Syria are revised: E. demissa, E. insulata and E. nigropilosa. Lectotypes for Empis insulata Collin, 1937 (Syria) and E. demissa Collin, 1949 (Egypt) are designated. A key to species of Empis s. str. of Egypt, Israel and Syria is provided.